The Evaluation Of Warehouse Receipt System Object Regulation: A Perspective Study Of Commodity Goods Concept In Indonesia - Hidayah, Khoirul; Nasyi'ah, Iffaty; Fidhayanti, Dwi (JURNAL LEGALITAS, 2022)
There are normative issues related to the concept of commodity goods with the object of warehouse receipts and social issues regarding the benefits of warehouse receipts for grain or rice farmers. Therefore, it is necessary to evaluate the regulation of the object of the warehouse receipt system so that it has a unique contribution to small farmers. The research applied in this research is juridical-empirical with a qualitative approach. The fact shows that rice farmers do not want to use the Warehouse Receipt System (WRS) because of the high cost and tend to choose the People's Business Credit program. Based on the study of the concept of commodities and benefits, it is necessary to change regulations related to the concept of WRS objects so that it is better to equate it with the concept of commodities. Grain or rice is a staple food that is excluded from the WRS object following the commodity concept because it has access to subsidies and special incentives from the government for national food security. Smallholders do not need to store rice in warehouses as in the WRS procedure to gain access to credit. This study shows that the government is reviewing the regulation of WRS objects in Indonesia so that it is beneficial for small farmers in particular.